Analysis of Function and Efficiency of Corn Marketing Channels in Jatirejo District, Mojokerto Regency, East Java Province - Anam, Khoirul; Ikka, Ni Dewi Ambal; Aditya, Dipa; Kusumawati, Nur Farida (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2025)
This study aims to determine the function and efficiency of corn marketing channels in Jatirejo District, Mojokerto Regency, East Java. The method used in sampling research purposive sampling by determining a sample of 25 farmers. This study also uses the method snow ball sampling to trace the marketing institutions and marketing channels formed based on information from farmer producers who were met randomly in the research area. The results of the study showed that there was 1 (one) dominant marketing channel in corn marketing in Jatirejo District, Mojokerto Regency. The marketing institutions involved include farmers, collectors, wholesalers and retailers. The marketing functions carried out by the marketing institution include the functions of selling, buying, transportation, processing, storage, provision of dryer machines, warehouses, price information, funds and handling marketing risks. The corn marketing channel in Jatirejo District has a marketing margin of Rp. 2.700/kg or equivalent to 34.52% and a farmer's share of Rp. 5.100/kg or equivalent to 65.38%. While the Marketing Efficiency level reaches 15.90% so that the corn marketing channel in Jatirejo District can be categorized as efficient.